(untitled) (Proceedings of the International Conference on Education, 2022)
Universities can improve their output (and standings) by looking closer at their inputs. Better-prepared students can utilize the opportunities presented, positively challenge Faculty and represent their institution as professionals in a productive manner. Thus, tertiary education stakeholders can identify areas that need addressing by looking at Thai students’ preparedness for university. This semi-exploratory study uses a mixed-method approach, including a survey of undergraduates at one Thai university, a focus group, interviews with two university students’ parents and the author’s experience. Students need better information about programs and universities, with most still relying on friends and family to make their selection. Online information seems general and does not provide the individual touch required. Thorough self-assessment is limited, with students trusting their elders. Societal pressure is great; thus, following what others do takes precedent; hence few learners take a gap year or enter university later in life. Program inflexibility (for example, credit transfers or changing majors) means students stick to programs that they are uncomfortable with. Thai universities need greater outreach as personal contact is crucial in students’ selection. Hence, supporting connections with relevant online information, onboarding and pre-university activities. Programs and universities appear to put their interest rather than the students, with students unable to change programs after entering. Program flexibility is necessary to accommodate learners who realize they may be suited for something else. Parents have an outsized influence on students; thus, educating parents is also required. More information on post-secondary education is needed, such as technical qualifications instead of degrees. A more holistic approach to preparedness is needed to have a more meaningful impact from university graduates.